IMPROVING STUDENTS' LEARNING OUTCOMES IN MATHEMATICS SUBJECTS ON THE CONCEPT OF FRACTION NUMBERS THROUGH THE STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) METHOD (Classroom Action Research at SDN Saruni 1) - Indriani, Arina Nur (Cakrawala Pedagogik, 2024)
This research is a classroom action research, with steps of planning, action and reflection. The sample in this study were 21 students of grade V SDN Saruni 1, Majasari District. The results of the study showed that by using the Student Team Achievement Divisions (STAD) Cooperative Type, student learning outcomes in each cycle increased between cycles I and II. This increase can be seen from the completeness of student learning in cycles I and II. In cycle I, student learning completeness only reached 62%, while in cycle II, student learning completeness had increased to 95%, this indicates that there has been an increase in student learning outcomes in mathematics at SDN Saruni 1, Majasari District, Pandeglang Regency.